Preliminary inventory of mammals from Yurubí National Park, Yaracuy, Venezuela with some comments on their natural history. - García, Franger J. (2012)
In Venezuela, mammals represent an important group of wildlife with high anthropogenic pressures that threaten their permanence. Focused on the need to generate baseline information that allows us to contribute to document and conserve the richness of local wildlife, we conducted a mammalogical inventory in Yurubí National Park, located in Yaracuy State in Venezuela. We carried out fieldworks in three selected vegetation types: an evergreen forest at 197m, a semi-deciduous forest ranging between 100-230m, and a cloud forest at 1 446m. We used Victor, Sherman, Havahart and pitfall traps for the capture of small non-volant mammals and mist nets for bats. In addition, we carried out interviews with local residents and direct-indirect observations for medium-large sized mammals. At least 79 species inhabit the area, representing 28% of the species recorded for the North side of the country. Chiroptera (39 spp.), Carnivora (13 spp.) and Rodentia (9 spp.) were the orders with the highest richness, as expected for the Neotropics. The evergreen forest had the greatest species richness (n=68), with a sampling effort of 128 net-hours, 32 bucket-days, 16 hours of observations, and three persons interviewed, followed by cloud forest (n=45) with 324 net-hours, 790 traps-night, 77 bucket-days, 10 hours of observations, and one person interviewed. The lowest richness value was in the semi-deciduous forest (n=41), with 591 traps-night, 15 net-hours, 10 hours of observations and three persons interviewed. Data and observations obtained in this inventory (e.g., endemism, species known as ?surrogate species? threatened in Venezuela) give an important role at the Yurubí National Park in the maintenance and conservation of local ecosystems and wildlife, threatened by human pressures in the Cordillera de la Costa.